Effect of Different Light Conditions on The Growth of Potato (Solanum Tuberosum L.) Variety Granola L. in Invitro - Rachmad Hersi Martinsyah; Yuyun Aprillonza; Lefriandi Arif Rahman (JERAMI : Indonesian Journal of Crop Science, 2024)
Potatoes are crops that have economic value and are rich in benefits because they contain good and relatively beneficial substances. In the production of the Granola L potato variety, tissue culture propagation is used. Many factors affect the growth and development of potato plants, one of which is light. Light is needed by plants to perform photosynthesis, and the photosynthate will be distributed to all parts of the plant through the transport network. The purpose of this research is to see the effect of various light conditions on the growth of Granola L potato explants. The design used is a Completely Randomized Block Design with variance analysis and further testing using Duncan's Multiple Range Test. The treatments used are neon light (1000 lux) (A), room light (250 lux) (B), and no light (C). The variables observed were the number of living explants, plant height, number of leaves, and root length. Observations showed that the number of living explants is strongly influenced by the planting media and the environment, which must be sterile. For the variables of plant height and root length, the highest data were shown by treatment C compared to treatments A and B. This is because the explants experienced etiolation, leading to stem and root elongation. For the number of leaves, the highest data were shown by treatment A, followed by treatment B, and the lowest by treatment C. Therefore, for good growth, Granola L potato explants require light.